2019
DOI: 10.1007/s00122-019-03336-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of the Fusarium head blight resistance QTL Qfhs.ifa-5A identifies two resistance QTL associated with anther extrusion

Abstract: Key message Fine-mapping separated Qfhs.ifa-5A into a major QTL mapping across the centromere and a minor effect QTL positioned at the distal half of 5AS. Both increase Fusarium resistance and anther extrusion. Abstract The Fusarium head blight (FHB) resistance QTL Qfhs.ifa - 5A resides in the low-recombinogenic pericentromeric region of chromosome 5A making fine-mapping particularly arduou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 69 publications
5
72
0
Order By: Relevance
“…Results of Panel 2 and Panel 3 displayed that complete cleistogamy, as found in cultivar Aveia, or a high level of chasmogamy, such as in Schenkenfeldener, resulted in lower infection levels and mycotoxin accumulation, but there are several known and unknown factors interfering with AR and mycotoxin accumulation. A precise evaluation of the impact of AR on mycotoxin content will require tests in oat populations with less variation in PH and flowering date, but high variability in AR, as recently used in wheat (Steiner et al, 2019). Our results indicate that differences in AR in oats explained only a small part of genetic variability for resistance to Fusarium, and more research is needed to disassemble and depict the active and passive resistance components against Fusarium in this smallgrain cereal.…”
Section: Flowering Traits and Fusarium Avoidancementioning
confidence: 81%
See 1 more Smart Citation
“…Results of Panel 2 and Panel 3 displayed that complete cleistogamy, as found in cultivar Aveia, or a high level of chasmogamy, such as in Schenkenfeldener, resulted in lower infection levels and mycotoxin accumulation, but there are several known and unknown factors interfering with AR and mycotoxin accumulation. A precise evaluation of the impact of AR on mycotoxin content will require tests in oat populations with less variation in PH and flowering date, but high variability in AR, as recently used in wheat (Steiner et al, 2019). Our results indicate that differences in AR in oats explained only a small part of genetic variability for resistance to Fusarium, and more research is needed to disassemble and depict the active and passive resistance components against Fusarium in this smallgrain cereal.…”
Section: Flowering Traits and Fusarium Avoidancementioning
confidence: 81%
“…Since oats are most susceptible to Fusarium infection during flowering (Tekle et al, 2012;Xue et al, 2015), and also because of the colocation of QTLs for AR and FHB in wheat (Steiner et al, 2019), a significant effect of AR on mycotoxin accumulation in oats was hypothesized. Results of Panel 2 and Panel 3 displayed that complete cleistogamy, as found in cultivar Aveia, or a high level of chasmogamy, such as in Schenkenfeldener, resulted in lower infection levels and mycotoxin accumulation, but there are several known and unknown factors interfering with AR and mycotoxin accumulation.…”
Section: Flowering Traits and Fusarium Avoidancementioning
confidence: 99%
“…It is now possible to identify genomic regions that contain genes, referred to as quantitative trait loci (QTLs) and single nucleotide polymorphism markers for FHB resistance derived from QTL mapping and genome-wide association studies. Ultimately, this will contribute to the selection of genotypes and cultivation of plants resistant to mycotoxin-producing pathogens [166,176].…”
Section: Resistance Breeding and Varieties Selectionmentioning
confidence: 99%
“…In the aforementioned studies, numerous QTL for AE were identified, and many of them were reported to be responsible for both AE and FHB [4,5,9,33]. In this regard, the well-known ones are those on 4BS and 4DS, linking to Rht-B1 and Rht-D1 [9], respectively, as well as the closely linked ones on 5AS and 5Ac in the Fhb5 region [5,34]. Considering the close relationship of AE with Type I FHB resistance, the former was proposed as a morphological marker for FHB resistance by many researchers [4,10].…”
Section: Ae As a Morphological Marker For Fhbmentioning
confidence: 99%